Comparative Analysis of Arabic Language Learning Management in Formal and Non-Formal Educational Institutions - Khoeriyah Ajeng Prasasti; Ahmadi; Ali Samaila (Uktub, 2025)
This research aims to describe the differences in Arabic language learning management in formal and non-formal educational institutions. This research uses a qualitative descriptive approach with a library research approach. The data collection method used is to collect various kinds of data from articles, books and other reading. The results of the research show that: Formal and non-formal educational institutions have their own Arabic language learning management, which refers to the learning achievement goals at each institution. The difference in focus aspects in each institution is something that occurs due to differences in the scope and targets of each institution.